The relationship of auditor competence and independence on audit quality: An assessment of auditor ethics moderation and professional commitment - Pattiasina, Victor; Noch, Muhamad Yamin; Surijadi, Herman; Amin, Muhammad; Tamaela, Eduard Yohannis (Indonesia Accounting Journal, 2021)
The purpose of this study is to examine and analyze the effect of auditor competence and independence on audit quality as moderated by auditor ethics and professional commitment. The population of this study is the BPKP Auditor Representative of Papua Province with census sampling as the sampling method. Data collection was carried out by direct survey. Hypothesis testing was tested empirically using Moderated Regression Analysis. The results of the study have proven that the competence and independence of auditors has a positive and significant effect on audit quality at BPKP Representatives of Papua Province. It is evidenced by the regression coefficient, which shows that the increase follows competence or independence of auditors increases, as well as the increase of audit quality. The results of this study also show that the interaction or influence of auditor ethics does not moderate the effect of auditor competence on audit quality at BPKP Representatives of Papua Province. Moreover, the interaction of professional commitment does not moderate the effect of auditor independence on audit quality. It is believed that the factor caused the phenomena is that the auditors of BPKP Representative of Papua Province have good values or fundamental principles of ethics as well as professional commitment. The values that have been held so far are relatively relevant or have a lot in common with the auditorsâ€™ ethics and professional commitment.Â